The Application of Ionic Nanoparticles in the Conservation of Archaelogical Wood. Issue 1 (March 2014) - Chadwick, Alan V.; Howland, Kevin; Went, Michael J.; Schofield, Eleanor J.; Jones, A. Mark; Klumperman, Bert; Mallon, Peter; Pasch, Harald; van Reenen, Albert
Summary A potential method for the de‐acidification of water‐logged archaeological wood is through a treatment with alkaline nanoparticles. In previous studies, we have shown that strontium carbonate nanoparticles are especially effective in removing sulfuric acid from the Mary Rose timbers. In this contribution, we report the effect of these nanoparticles on other known sulfur compounds in the timbers. Overall, these effects are beneficial, yielding benign compounds and removing the possibility for the conversion to sulfuric acid.